Towards Sustainable Middle Eastern Cities: A Local Sustainability Assessment Framework (Journal of University of Babylon for Engineering Sciences, 2019)
To assist in making Middle Eastern cities more sustainable a guiding methodological framework for local sustainability assessment is key to achieving a sustainable future. This paper investigates available frameworks and develops an approach to local sustainability assessment (LSA), by constructing a methodological framework utilising a combination of (bottom-up) and (top-down) approaches. This facilitates the formulation, selection and prioritisation of key indicators, which can then guide the assessment of a city’s sustainability at a local level in the Middle East. The paper finally applies the LSA methodological framework to the Iraqi city of Hilla and succeeds in formulating and ranking 57 useful and valid sustainability indicators.